Differences in game-related statistics between winning and losing teams in women's basketball - Gomez, M. A.; Lorenzo, A.; Sampaio, J.; Ibanez, S. J. (Journal of Human Movement Studies, 2006)
The aim of the present study was to identify the game-related statistics that allow discriminating between winning and losing teams in women's basketball. The sample comprised all 178 regulär season games from the 2004/2005 Spanish Women's League and the game- related statistics included: 2 and 3-point field-goal and free-throw percentages, offensive and defensive rebounding percentage, blocks, assists, fouls, turnovers and steals. Results showed that in all games, the game-related statistics that discriminated between both groups were the 2 and 3-point field-goals percentages, steals and assists. In balanced games (final score differences equal or below 12 points), the discriminant game-related statistics were the 3-point field-goal percentages, assists and fouls. In unbalanced games (final score differences above 12 points) the discriminant game-related statistics were the 2 and 3 points field-goals percentages, assists and steals. The 3-point field-goal percentages and the assists were the only game-related statistics common to all three analyses.